Protamine Impact on Viability of Bacterial and Eukaryotic Cell Cultures - Klabukova, D. L. (Asian Journal of Pharmaceutics (AJP), 2017)
Objective: At present time, the substitution of the natural ingredients for various chemical additives used in food industry is an important problem. The perspective of this direction is protamine - small nuclear protein germ cells number of organisms. The article reveals the influence of protamine from salmon fish on the typical strains growth of pathogenic microorganisms and the viability of eukaryotic cell cultures. Materials and Methods: Expressed bactericidal activity of protein in concentration 4000 mcg/mL in regard to microbial strains Escherichia coli K-12 C 600 and Salmonella typhimurium LT2 was set up. Results: Significant antiproliferative effect on tumor cell lines Hep-2, RD, A-549, and T-98 G was marked, and less effect was found on line of human fetal lung fibroblasts FLECH 900/14. Conclusion: This makes possible the use of protamine as a promising antimicrobial and antitumor agent, for example, food additives with functional orientation.